MONITORING OF MEDICINE THERAPY IN DM (Diabetes Mellitus) PATIENTS, MELENA, ANEMIA, HIPOALBUMIN AND SEPSIS IN HOSPITAL “ X ” - sari, dini permata (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2023)
Diabetes Mellitus (DM) is a group of chronic metabolic diseases with hyperglycemia characteristics, this disease can attack several organs of the body causing various complaints. Diabetes Mellitus (DM) is a disease characterized by blood sugar levels. Physical activity is any body movement produced by skeletal muscles that requires energy. Lack of physical activity is an independent risk factor for chronic disease. This study aims to determine the effect of physical activity on blood sugar levels in patients with diabetes mellitus. Sepsis is the invasion of pathogenic microorganisms or their toxins into the blood or other tissues, resulting in an exaggerated systemic response to infection, which causes a collection of clinical symptoms and ends in a life-threatening state of organ dysfunction. Anemia is indeed not a direct complication caused by Type 2 DM, but in patients with diabetes, diabetes can damage blood vessels in the body and can cause kidney problems in the long term if not controlled. Impaired kidney function can cause anemia. Melena is a condition when the stool becomes dark or black in color, which is caused by bleeding in the upper gastrointestinal tract. Hypoalbuminemia in critical illness is an important marker of mortality. The pathophysiology of hypoalbuminemia in critical illness including decrease of production, inflammation marker, vascular leakage, and malnutrition. Administration of intravenous human albumin is needed to be considered for treatment of hypoalbuminemia in critical illness.This report was conducted to find out drug related problems (DRP's) in the treatment management of DM (Diabetes Melius) Patients, Melena Anemia, Hipoalbumin and Sepsis at “ X “ Hospital. The patient on behalf of Mrs.R.M was treated in the inpatient room. Drug Therapy Monitoring to ensure rational use of drugs, so that unwanted events do not occur.